Exposure assessment to mycotoxins in a Portuguese fresh bread dough company by analysis of dust and urine samples - Viegas, Susana (2018)
Occupational exposure to mycotoxins can occur in many and different work environments. Critical workplaces for mycotoxins appearance have already been studied and nowadays it is possible to investigate that exposure to mycotoxins is likely through inhalation due to their presence in dust. This study aimed to assess occupational co-exposure to mycotoxins in a fresh bread dough company, an workplace not studied until now.